2015
DOI: 10.17116/neiro201579591-101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines for the use of intraoperative fluorescence diagnosis in brain tumor surgery

Abstract: In this paper, we present a review of current literature on the application of intraoperative fluorescence diagnosis and fluorescence spectroscopy using 5-aminolevulinic acid in surgery for various types of brain tumors, both alone and in combination with other neuroimaging methods. Authors' extensive experience with these methods allowed them to develop a set of clinical guidelines for the use of intraoperative fluorescence diagnosis and fluorescence spectroscopy in surgery of brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
0
8
0
2
Order By: Relevance
“…Most studies on glioma surgery with 5-ALA fluorescence for guidance have documented increases in tumor resection area ( 109 , 110 ). The results of a phase III study indicated a 1.5-month increase in progression-free survival with 5-ALA fluorescence-guided surgery ( 111 ).…”
Section: Fluorescent Dyes In Neurosurgerymentioning
confidence: 99%
“…Most studies on glioma surgery with 5-ALA fluorescence for guidance have documented increases in tumor resection area ( 109 , 110 ). The results of a phase III study indicated a 1.5-month increase in progression-free survival with 5-ALA fluorescence-guided surgery ( 111 ).…”
Section: Fluorescent Dyes In Neurosurgerymentioning
confidence: 99%
“…Presently, various intraoperative technologies (ultrasound, magnetic resonance imaging, fluorescence imaging) are commonly used in surgical treatment of gliomas; these techniques are aimed at improving safety and radicality of the tumor removal [1][2][3][4]. Recent studies demonstrated that the volume of tumor resection significantly correlates with life expectancy of patients in this group [5][6][7][8].…”
Section: сLinical Medicinementioning
confidence: 99%
“…These kinds of tumor can be characterized by aggressive infiltrative growth into the surrounding brain tissues and thereby the absence of clear boundaries between the cancer and non-cancer tissues, which makes it difficult to distinguish them during surgery in order to minimize the required extent of tumor resection. The introduction of intraoperative fluorescence diagnostics into clinical practice allows a significant enhancement of the ability to identify any remaining tumor, thereby increasing the survival rate [5][6][7][8][9]. Also, clinical testing of fluorescence techniques [10][11][12] has demonstrated the limitations of using only white light microscopy for achieving total tumor resection, and the requirement for using additional technologies for detecting the "cancer/non-cancer" dividing line.…”
Section: Introductionmentioning
confidence: 99%